Improvised perioperative techniques to meet the challenges of microvascular free flap surgery - Pathak, Soumi; Chowdhury, Itee; Bhargava, Ajay Kumar (Journal of Society of Anesthesiologists of Nepal, 2016)
Deformities of the head and neck region after radical oncosurgery can have devastating effects on the appearance of the patient with significant impact on patients quality of life. Reconstruction of such defects continues to be an extremely demanding challenge for plastic surgeons who aim to restore form and function with minimal surgical morbidity. The purpose of this communications is to highlight the various interventions and the protocols that are adopted to decrease the free flap failure rate.